Mortality prediction of retinal vessel diameters and function in a long-term follow-up of haemodialysis patients. Issue 16 (16th May 2022) - Günthner, Roman; Streese, Lukas; Angermann, Susanne; Lorenz, Georg; Braunisch, Matthias C; Matschkal, Julia; Hausinger, Renate; Stadler, David; Haller, Bernhard; Heemann, Uwe; Kotliar, Konstantin; Hanssen, Henner; et al.
Abstract: Aim: Retinal vessel diameters are candidate biomarkers of mortality prediction in large population-based studies. We aimed to investigate the predictive value of retinal vessel diameters and flicker-induced retinal arteriolar and venular dilation on all-cause mortality in long-term follow-up of haemodialysis patients. Methods and results: Retinal vessel diameters as well as maximum arteriolar (aMax) and venular dilation (vMax) were investigated in 275 and 214 haemodialysis patients, respectively. Patients were observed in a long-term follow-up for a median period of 73 months. About 36% (76/214) and 41% (113/275) of patients died. Arteriolar and venular diameters were 175 ± 19 and 208 ± 20 µm, respectively. Median aMax and vMax were 1.6 (0.3–3.3) and 3.2 (2.0–5.1)%. Patients within the lowest tertile of vMax showed lower 5-year survival rates compared with the highest tertile (50.6 vs. 82.1%) and also exhibited a higher incidence of infection-related deaths (21.7 vs. 4.0%). Univariate hazard ratio (HR) per standard deviation increase of vMax for all-cause mortality was 0.69 (0.54–0.88) and was even more pronounced for infection-related mortality [HR 0.53 (0.33–0.83)]. Regarding all-cause mortality, multivariate adjustment for eight non-retinal mortality predictors including interleukin-6 did not attenuate the HR relevantly [0.73 (0.54–0.98)]. Arteriolar and venular diameters did not predict all-cause nor cardiovascular and infection-related mortality. Conclusions: Long-term follow-up of patients on haemodialysis demonstrated the potential of retinal venular dilation capacity for mortality prediction, which was most pronounced for infection-related mortality. In the same cohort, retinal arteriolar and venular diameters showed no predictive value for hard endpoints. Retinal venular dilation but not arteriolar and venular diameters is a valuable diagnostic biomarker for risk prediction in patients with end-stage renal disease and should be considered for monitoring of critically ill patients. Graphical Abstract: Graphical Abstract